Mediastinal primary neuroendocrine tumor - García-Ramos, Hugo Michael (2020)
This the case of a 49-year-old male patient with no relevant history or harmful habits, chest pain, light-effort dyspnoea and anterior mediastinal mass. He was operated on, with pathology and immunohistochemistry compatible with primary large cells neuroendocrine carcinoma of mediastinum. Treatment wascompleted with chemotherapy and radiation therapy, with good clinical evolution.